2008
DOI: 10.1111/j.1479-828x.2008.00893.x
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study of outcomes five years after hysterectomy in premenopausal women

Abstract: The long-term health of women who undergo hysterectomy is not noticeably different from a group of women who do not undergo hysterectomy. In women undergoing hysterectomy, pelvic pain, urinary frequency and depression scores are reduced five years after hysterectomy compared to prehysterectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
6

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 30 publications
0
12
0
6
Order By: Relevance
“…45 Despite the fact that androgen levels were similar between the groups, it was of utmost interest to see SM per se standing out as an independent predictor of SD. Whether the accompanying hysterectomy itself is in part to blame for the higher prevalence of SD in the SM group, while disputible, [46][47][48][49] this is beyond the scope of this work, and even then does not negate the independent and significantly untoward effect of surgery on sexual functioning. Another plausible explanation for the difference in the prevalence of SD between the groups could be possible differences in sexual functioning at baseline, which could not be depicted by our cross-sectional study design, which also is an important limitation of our study.…”
Section: Discussionmentioning
confidence: 87%
“…45 Despite the fact that androgen levels were similar between the groups, it was of utmost interest to see SM per se standing out as an independent predictor of SD. Whether the accompanying hysterectomy itself is in part to blame for the higher prevalence of SD in the SM group, while disputible, [46][47][48][49] this is beyond the scope of this work, and even then does not negate the independent and significantly untoward effect of surgery on sexual functioning. Another plausible explanation for the difference in the prevalence of SD between the groups could be possible differences in sexual functioning at baseline, which could not be depicted by our cross-sectional study design, which also is an important limitation of our study.…”
Section: Discussionmentioning
confidence: 87%
“…In a two-year prospective observational study in Egypt, Helmy et al found an increase in the risk of depression in women who undergo hysterectomy for benign conditions, whether they had psychiatric comorbidity before surgery or not (Helmy et al, 2008). However, other studies have reported no negative effects on the psychological condition of women after hysterectomy performed for non-malignant causes (Darwish et al, 2014;Farquhar et al, 2008;Gibson et al, 2012;Persson et al, 2010;Yen et al, 2008). In a prospective study conducted by Yen et al in Taiwan, they found an improvement in depressive symptoms after four months in 68 women who underwent hysterectomy for nonmalignant conditions, which differs from our results.…”
Section: Discussionmentioning
confidence: 93%
“…Se ha evidenciado que posterior a la HT por causa benigna, aparecen trastornos depresivos y/o ansiosos en las mujeres en frecuencias variadas. Para la detección de los trastornos psiquiátricos como depresión y/o ansiedad se utilizan diversas herramientas de medición en los estudios analizados 4,9,10,11,12,13,14,15,16,17 , las que miden diversos factores desencadenantes en los trastornos psiquiátrico depresivos y/o ansiosos.…”
Section: Medición Y Prevalencia De Trastornos Depresivos Y/o Ansiososunclassified
“…En relación a estudios prospectivos cuantitativos, diversos autores han investigado la continuidad de estos trastornos, realizando un seguimiento desde 1 mes posterior a la cirugía hasta un máximo de 5 años después del procedimiento. En estos estudios se observa que, a partir de los 3 meses posterior a la cirugía, se reportan mejoras desde un 45% a más del 90% de las mujeres sometidas a HT 12,13 .…”
Section: Medición Y Prevalencia De Trastornos Depresivos Y/o Ansiososunclassified